Propostas de produção escrita em livros didáticos: uma análise sob a perspectiva dos gêneros - Karen Alves de Andrade (2011)
The inclusion of activities with a focus on textual genres in teaching has changed the dynamics of education in Portuguese Language. The importance of working the language in use, through texts in which genres are manifested, has mobilized educators who seek to adapt their practices to these new perspectives. However, there are still misconceptions in pedagogical practice. There are strong evidences that education professionals dont feel comfortable dealing with new teaching methods in native language. Thus, the traditional teaching persists, which means that the internalization of rules and a static view of language dominate the classroom. Even though it often happens, schools have earlier recognized the importance of the study of textual genres, including them in their pedagogical proposals. Publishers, likewise, filled his collections of textbooks with a multitude of different text genres, without working them effectively - taking into account its social function, evidenced both in form and content and also in the style of each genre. And in order to get results focused on improving teaching practices, this study sought to analyze collections of Portuguese language textbooks to see how the textual genres are worked in the proposals of text production. Considering that the production of texts will be an immediate product of the content developed in the classroom, we take the proposed compositions as an object of study to verify the production of genres that is being demanded of students and which particular production encompasses those activities. It was based on gaps shown on textbooks that we suggest an array of operations necessaries to the text production proposals, serving as a guide for the analysis that may contribute to future assessments.